High glutamine levels are related to increased mortality and blunted immune response in elderly septic patients - Di Girolamo, F.G.; Fiotti, N.; Castello, L.M.; Casarsa, C.; Lupia, E.; Mujesan, M.L.; Ronco, C.; Di Somma, S.; Avanzi, G.; Mearelli, F.; Biolo, G. (Nutrition (Burbank, Los Angeles County, Calif.), 2018)
Glutamine (GLN) is actively taken-up and utilized by immune cells in critical illness [1,2]. We have hypothesized that variability of plasma GLN levels in elderly septic patients is linked to degree of immunoactivation and outcome.